DNA barcoding of elasmobranchs from Indian Coast and its reliability in delineating geographically widespread specimens. (12th September 2013) - Pavan-Kumar, A.; Gireesh-Babu, P.; Suresh Babu, P. P.; Jaiswar, A. K.; Prasad, K. Pani; Chaudhari, Aparna; Raje, S. G.; Chakraborty, S. K.; Krishna, Gopal; Lakra, W. S.
Abstract: Identification of elasmobranchs by conventional taxonomy is difficult due to similarities in morphological characters. Species-specific molecular markers are good choice for identifying species irrespective of it's life stage. Recently, mitochondrial cytochrome c oxidase subunit I (COI) gene got global recognition as a barcode gene to discriminate all animals up-to species level. In this study, mitochondrial COI partial gene was used to develop DNA barcodes for 18 species of elasmobranchs (10 species of sharks and 8 species of rays). The COI barcodes clearly distinguished all the species with high interspecific distance values than intraspecific values. The average interspecific and intraspecific distance values are 8.6% and 0.3% for sharks, respectively and 12.4% and 0.63% for rays, respectively using K2P method. The Neighbor-Joining tree showed distinct clusters shared by the species of same genera. The COI barcodes were also used to estimate allopatric divergences for selected species across broad geographical locations and found that Sphyrna lewini, Aetobatus narinari and Neotrygon kuhlii have cryptic diversity.